Work-Family Conflict, Part II: Job and Life Satisfaction in National Collegiate Athletic Association Division I-A Certified Athletic Trainers - Mazerolle, Stephanie M (The National Athletic Trainers' Association, Inc, 2008)
CONTEXT: Previous researchers have shown that work-family conflict (WFC) affects the level of a person's job satisfaction, life satisfaction, and job burnout and intentions to leave the profession. However, WFC and its consequences have not yet been fully investigated among certified athletic trainers. OBJECTIVE: To investigate the relationship between WFC and various outcome variables among certified athletic trainers working in National Collegiate Athletic Association Division I-A settings. DESIGN: A mixed-methods design using a 53-item survey questionnaire and follow-up in-depth interviews was used to examine the prevalence of WFC. SETTING: Division I-A universities sponsoring football. PATIENTS OR OTHER PARTICIPANTS: A total of 587 athletic trainers (324 men, 263 women) responded to the questionnaire, and 12 (6 men, 6 women) participated in the qualitative portion of the mixed-methods study. DATA COLLECTION AND ANALYSIS: We calculated Pearson correlations to determine the relationship between WFC and job satisfaction, life satisfaction, and job burnout. Regression analyses were run to determine whether WFC was a predictor of job satisfaction, job burnout, or intention to leave the profession. Interviews were transcribed verbatim and then analyzed using the computer program N6 as well as member checks and peer debriefing. RESULTS: Negative relationships were found between WFC and job satisfaction (r  =  −.52, P < .001). Positive were noted between WFC and job burnout (r  =  .63, P < .001) and intention to leave the profession (r  =  .46, P < .001). Regression analyses revealed that WFC directly contributed to job satisfaction (P < .001), job burnout (P < .001), and intention to leave the profession (P < .001). CONCLUSIONS: Overall, our findings concur with those of previous researchers on WFC and its negative relationships to job satisfaction and life satisfaction and positive relationship to job burnout and intention to leave an organization. Sources of WFC, such as time, inflexible work schedules, and inadequate staffing, were also related to job burnout and job dissatisfaction in this population.